The latest amendments in the foreign investment law in Saudi Arabia - Alshahrani, Sarah (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2019)
The recent reforms in the foreign investment law in the Kingdom of Saudi Arabia (KSA), as well as the recent drop in foreign direct investment (FDI) into the country, were the main motivation for conducting this research. Although KSA is one of the leading countries known to have attracted FDI, such a drop should be considered seriously. The main objective of the study, therefore, is to conduct a critical analysis of the foreign investment law in KSA. This analysis highlights how the Implementation Regulation (IR 2014) of the FIA has attempted to overcome some shortcomings by introducing a new provision requiring post-investment monitoring. However, the IR does not overcome all the weaknesses of its previous version. For instance, although it brings important new changes to the investment climate, such as speeding up the procedure for granting an investment licence, in practice there are still delays and a long process.